N,N-Bis(diphenylphosphanyl)cyclobutanamine - Engelbrecht, Ilana (International Union of Crystallography, 2011)
In the title compound, C(28)H(27)NP(2), the N atom adopts an almost planar geometry with the two P atoms and the C atom attached to it, with a distance of 0.066 (2) Å between the N atom and the C/P/P plane. The distorted trigonal–pyramidal geometry of the N atom is further illustrated by bond angles ranging between 115.22 (11) and 123.53 (8)°. Bond angles varying from 99.99 (9) to 108.07 (9) ° are indicative of the distorted pyramidal environment around the P atoms. An intramolecular C—H⋯P hydrogen bond occurs. In the crystal, intermolecular C—H⋯π interactions link the molecules into a supramolecular network.